2005
DOI: 10.1037/1099-9809.11.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Cultural Exposure and Development of Korean Perspective-Taking Ability for Transracially Adopted Korean Children.

Abstract: This study investigated the benefits of cultural exposure for transracially adopted (TRA) Korean children's developmental understanding of being Korean. Fifty TRA Korean children living in the United States were interviewed to assess their understanding of the implications of their Korean status for peer relations and personal identities, using a model of perspective-taking ability (PTA). Results showed cultural exposure and chronological age were significant predictors of children's PTA for being Korean. Cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
80
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 35 publications
(66 reference statements)
13
80
0
Order By: Relevance
“…Research suggests that same-race and transracially adopted children begin to become aware of racial differences, as well as their adoptive status, as early as 4-5 years of age (Brodzinsky, Singer, & Braff, 1984;Huh & Reid, 2000). As transracial adoptees grow older, Correspondence concerning this article should be addressed to Richard M. Lee Lee & Quintana, 2005). At the same time, they may begin to experience feelings of loss of birth culture and family history and the growing awareness of racism and discrimination in their everyday lives (Meier, 1999;Powell & Affi, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that same-race and transracially adopted children begin to become aware of racial differences, as well as their adoptive status, as early as 4-5 years of age (Brodzinsky, Singer, & Braff, 1984;Huh & Reid, 2000). As transracial adoptees grow older, Correspondence concerning this article should be addressed to Richard M. Lee Lee & Quintana, 2005). At the same time, they may begin to experience feelings of loss of birth culture and family history and the growing awareness of racism and discrimination in their everyday lives (Meier, 1999;Powell & Affi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…they develop a more coherent understanding of what it means to look physically different from their parents (D. C. Lee & Quintana, 2005). At the same time, they may begin to experience feelings of loss of birth culture and family history and the growing awareness of racism and discrimination in their everyday lives (Meier, 1999;Powell & Affi, 2005).…”
mentioning
confidence: 99%
“…In particular, D. C. Lee and Quintana (2005), in their sample of Korean adoptees in tbe United States, showed tbat BCS predicted adoptee's awareness of perspectives, attitudes, and experiences shared by Koreans. Cultural exposure bad a slightly stronger relation for younger adoptees than older ones.…”
Section: Adoption Culture Race and Icamentioning
confidence: 95%
“…Furthermore, another study indicated that transracial, international adoptees who engaged in cultural socialization were less likely to have delinquent behaviors (Johnston, Swim, Saltsman, Deater-Deckard, & Petrill, 2007). Exposure to cultural activities also increased transracial adoptive children's developmental understanding of culture and race (Lee & Quintana, 2005). In addition, cultural socialization also allowed for a child to have the skills to function, at least at a modest level, in their country of origin or with people from their country of origin (Thomas & Tessler, 2007).…”
Section: Cultural Socialization and Racial Socializationmentioning
confidence: 99%